2008
DOI: 10.1007/s00402-008-0790-8
|View full text |Cite
|
Sign up to set email alerts
|

Closed reduction of the pediatric supracondylar humerus fractures: the “joystick” method

Abstract: These results suggest that the "joystick" reduction method is a reliable alternative when closed reduction itself is not successful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 28 publications
1
26
0
1
Order By: Relevance
“…We found the study interesting because the technique described by the authors is similar to our previously published article [2], referred by the authors in the Introduction and Discussion sections of their study. Although their ''novel'' technique is very similar to ours with the idea of controlling the external rotation, coronal tilt, and translation of the proximal fragment by using the ''joystick'' K-wire, there are some slight modifications in the technique, which we cannot clearly understand.…”
Section: To the Editormentioning
confidence: 66%
See 1 more Smart Citation
“…We found the study interesting because the technique described by the authors is similar to our previously published article [2], referred by the authors in the Introduction and Discussion sections of their study. Although their ''novel'' technique is very similar to ours with the idea of controlling the external rotation, coronal tilt, and translation of the proximal fragment by using the ''joystick'' K-wire, there are some slight modifications in the technique, which we cannot clearly understand.…”
Section: To the Editormentioning
confidence: 66%
“…The authors stated that the study included 143 patients who were divided into two groups depending on whether treatment occurred before (Group 1, 90 fractures) or after Even so, we think this Level-III research paper is an important contribution to the literature proving the reproducibility and safety of our Joystick method [2], which was published earlier as a case series. We therefore would like to thank the authors for their interest in our work.…”
Section: To the Editormentioning
confidence: 97%
“…In 2009, Parmaksizoglu et al [11] described a method of reduction similar to our reported technique. Their technique involved placing a K-wire from laterally to medially in the humeral diaphysis, ''below the deltoid muscle.''…”
Section: Introductionmentioning
confidence: 64%
“…In fact, the 2.5 mm size is perfectly situated between the 2 mm and 3 mm pins utilized by Parmaksizoglu and colleagues [3]. Additionally, the terminal thread prevents translation and anterior protrusion versus a smooth pin.…”
Section: To the Editormentioning
confidence: 96%
“…Additionally, I appreciate the reference to their prior published ''joy-stick'' technique [3]. Finding more options and techniques to improve supracondylar humeral fracture care is to be encouraged [1].…”
Section: To the Editormentioning
confidence: 99%